Evaluasi Virulensi Virus Tungro dari Beberapa Daerah Endemi dan Uji Ketahanan Plasma Nutfah Padi - Suprihanto Suprihanto; I Nyoman Widiarta; Dede Kusdiaman (Jurnal Perlindungan Tanaman Indonesia, 2010)
The purpose of this study was to evaluate the level of tungro virus virulence from some endemic areas, the suitability of planting resistant varieties, and resistance of rice germplasms. Tungro virus isolates were collected from tungro-endemic areas in North Sumatra, West Java, Central Java, South Sulawesi, West Sulawesi and Central Sulawesi. Tungro virus isolates were then inoculated using green leafhoppers Nephotettix virescens (Distant) to five differential varieties: Tukad Petanu, Bondoyudo, Kalimas, Tukad Balian, and Tukad Unda, and TN1 (as susceptible check). Level of virulence of tungro virus isolates and suitability planting of resistant varieties can be evaluated. Tungro virus isolate which has the highest virulence was used to test of resistant of rice germplasms. Results of tungro virulence test can be distinguished that there are 4 variants of virulence, namely: 073 (Subang, Bulukumba, Bantaeng, andWest Sulawesi isolates), 033 (Simalungun, Temanggung, and Palu), 031 (Kuningan andMagelang), and virulence 013 (Lanrang isolate). Tukad Petanu was still appropriate varieties to be planted in throughout the tungro-endemic areas (North Sumatra, West Java, Central Java, South Sulawesi, West Sulawesi, and Central Sulawesi). Bondoyudo variety still suitables to be planted in the areas of Simalungun, Kuningan, Magelang, Temanggung, Lanrang, and Palu. While Tukad Unda variety still have the suitability of planting for areas Kuningan, Magelang, and Temanggung. Between 100 assesions of germplasm which were tested to high virulence of tungro (073) one resistant assession has been identified (Deli assesion), and as many as 25 assesions showed moderately resistant reaction.